GENDER INEQUALITY TOWARDS THE MALE DOMINATION IN THE MOVIE OF ENOLA HOLMES 2 - Yesiana Vianingrum; Winarti Winarti (FRASA: ENGLISH EDUCATION AND LITERATURE JOURNAL, 2024)
Gender inequality is a social problem where there is discrimination or unequal treatment between men and women in access to important resources in human life. The issue of male dominance and restrictions on rights and roles by patriarchal culture have successfully shaped the shackles and discrimination of women around the world. This discrimination is the basis for the feminist movements that emerged as a manifestation of the desire to fight for women's rights in social life. In this globalization era, social issues such as gender inequality are illustrated in the form of movies. The movie Enola Holmes is one example of an illustration of gender inequality in a patriarchal society. Enola Holmes 2 is what gave rise to the researcher's desire to conduct a deeper study on the issue of gender inequality. This study aims to analyze the forms of gender inequality and how the issue of gender inequality affects the female characters in the movie Enola Holmes 2. This study is a descriptive qualitative study, the primary data is taken from the movie Enola Holmes 2 itself and the secondary data is taken from the transcript of the movie. The researcher uses the theory of patriarchy by Walby (2017) to analyze the issue of gender inequality and feminism in the movie Enola Holmes 2. The results of this study are packaged in the form of a thesis entitled "Gender Inequality Towards Male Domination in The Movie Enola Holmes 2".